Towards an integrated weed management decision support system: A simulation model for weed-crop competition and control - Molinari, Franco A. (2020)
A mathematical simulation model for the multi-annual assessment of Integrated Weed Management strategies is presented. The model allows the simulation of the competitive interaction between annual weeds and crops. For weed development, the following processes are represented: (i) demographic dynamics on a daily basis considering the numeric composition of the different phenological states, (ii) intra and inter specific competition, (iii) seed production and (v) the effect of different control methods. For the crop development, the computed variables are: (i) Leaf Area Index, (ii) competitive effect over the weed, (iii) the expected yield as a function of weed competition. The model was developed in close collaboration with agricultural technicians and extensionists aiming to target a decision-making related audience. Results are provided for a wild oat (Avena fatua) – winter wheat (Triticum aestivum) / malting barley (Hordeum distichum) rotation system, typical of the Semiarid Pampean Region of Argentina. Multi-annual scenarios were generated to evaluate the effect of different management strategies against common herbicide-based practices in susceptible and resistant weed populations. Parts of the model were validated with independent experimental data. Finally, future improvements of the model and some guidelines towards the development of a long-term Decision Support System for weed management are provided.